Intelligent Video Surveillance System for Banks - Vijayan, N; Thomas, MP; Abraham, LA; Issac, E; Ubaid, S (International Journal of Computer Sciences and Engineering, 2025)
The paper proposes an Intelligent Video Based Surveillance System for motion detection in bank locker rooms. The system basically concern on the use of automatic motion detection technique using webcams for locker security. The system captures action triggered by motion as it happens. When an intrusion occurs the system will instantly send email notification with the image captured straight off to the security officer. The alert mechanism promptly triggers an audio clip alarm once motion is detected, and this facilitates the prevention of any sort of security breach at that instant.